EXPLORING THE EFFECTIVENESS OF ENGLISH SONGS AS A MEDIUM FOR DEVELOPING LISTENING ABILITY - Riska Humaera; Nurdin Noni; Yunitari Mustikawati; Muh Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study aims to analyze the effectiveness of using English songs in improving students' listening skills. The method used is quantitative with a quasi-experimental design, involving two grade XI classes at SMAN 1 Pangkep as research subjects. Grade XI Harmonis was designated as the experimental group that received treatment in the form of learning using Lenka's songs, while grade XI Cekatan was the control group that followed conventional learning. The instruments used included a listening test (pre-test and post-test) and a student learning interest questionnaire. The results of the analysis showed a significant difference between the post-test scores of the experimental and control groups, with a significance value of 0.000 <0.05. This indicates that the use of songs can effectively improve students' listening skills. In addition, the results of the questionnaire showed that most students had a high interest in using songs as a learning medium, which was reinforced by the results of the correlation test which showed a positive and strong relationship between student interest and improved listening skills (r = 0.649, p <0.05).Thus, the use of English songs, especially Lenka's works, has been proven to not only improve the cognitive aspect in listening learning, but also the affective aspects such as student motivation and involvement. Songs can be used as an effective alternative strategy in learning English